2021
DOI: 10.1007/s13337-021-00653-y
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2: phylogenetic origins, pathogenesis, modes of transmission, and the potential role of nanotechnology

Abstract: The COVID-19 pandemic has elicited a rapid response from the scientific community with significant advances in understanding the causative pathogen (SARS-CoV-2). Mechanisms of viral transmission and pathogenesis, as well as structural and genomic details, have been reported, which are essential in guiding containment, treatment, and vaccine development efforts. Here, we present a concise review of the recent research in these domains and an exhaustive analysis of the genomic origins of SARS-CoV-2. Particular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 119 publications
0
12
0
4
Order By: Relevance
“…Early phylogenetic studies on SARS-CoV-2 genomic sequences showed that it clustered closely with sequences originating from SARS-like viruses from bats within lineage B of the betacoronavirus genus. Lineage A groups are prototypical coronaviruses such as MHV and the human coronaviruses HCoV-HKU1 and HCoV-OC43 ( Figure 1 A,B) ([ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] tree.bio.ed.ac.uk/software/figtree/ accessed on 7 July 2021) (Software (ed.ac.uk accessed on 7 July 2021)), while the other highly pathogenic coronavirus, MERS-CoV, is found within lineage C, along with the related camel-derived MERS-CoV ([ 41 , 42 ] and references therein). The S protein amino acid sequences from four representative beta coronaviruses (HCoV-HKU1, MHV, SARS-CoV, and MERS-CoV) were aligned and the solved S protein structures were compared to determine their amino acid identity and the overall structural organization similarities among these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Early phylogenetic studies on SARS-CoV-2 genomic sequences showed that it clustered closely with sequences originating from SARS-like viruses from bats within lineage B of the betacoronavirus genus. Lineage A groups are prototypical coronaviruses such as MHV and the human coronaviruses HCoV-HKU1 and HCoV-OC43 ( Figure 1 A,B) ([ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] tree.bio.ed.ac.uk/software/figtree/ accessed on 7 July 2021) (Software (ed.ac.uk accessed on 7 July 2021)), while the other highly pathogenic coronavirus, MERS-CoV, is found within lineage C, along with the related camel-derived MERS-CoV ([ 41 , 42 ] and references therein). The S protein amino acid sequences from four representative beta coronaviruses (HCoV-HKU1, MHV, SARS-CoV, and MERS-CoV) were aligned and the solved S protein structures were compared to determine their amino acid identity and the overall structural organization similarities among these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms are genetic code variations shared by many individuals and can confer evolutionary advantage or disadvantage through natural selection. In regard to the novel coronavirus, there are two mammalian proteins that are key to viral susceptibility: angiotensin-converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TM-PRSS2) [66,67]. ACE2 is a transmembrane protein on lung cell and other tissue surfaces that acts as the SARS-CoV-2 viral receptor and allows viral endocytosis [67,68].…”
Section: Predicting Susceptibilities: Tmprss2 and Ace2mentioning
confidence: 99%
“…The basis for this variation is at least in part due to the ease with which the virus' envelope spike proteins can bind to the polymorphic ACE2 receptor [70,71]. These variations in functionality are dependent not only on the presence and activity of TMPRSS2 [75], but also on the interactions of the spike protein with specific amino acids that make up the ACE2 receptor [66]. Between 62% and 99% of the amino acid sequence for the ACE2 receptor is conserved across at least 23 mammalian species, including humans, dogs, cats, pigs, cattle, sheep, horse, and ferrets [71].…”
Section: Predicting Susceptibilities: Tmprss2 and Ace2mentioning
confidence: 99%
“…This binding is followed by cleavage of the spike protein by certain proteases (TMPRSS2 and furin) leading to the membrane fusion to the host cell. It facilitates viral genome entry into the host cell [4,5]. The virus takes over the host machinery to replicate its genome and facilitates the formation of a multi-subunit replicase-transcriptase complex (RTC), which transcribes to generate new viral RNA.…”
Section: Introductionmentioning
confidence: 99%